FORMATION OF READINESS OF FUTURE TEACHERS OF HISTORY FOR INNOVATIVE ACTIVITY IN SCHOOL USING THE "PROJECT METHOD" (Pedagogy of Higher and Secondary Education, 2009)
Article is devoted questions of preparation of the future teachers of history to the qualified activity in the conditions of a modern information field lo information-technical component will be a question of formation of information competence of the future teacher of history, in particular.